2015
DOI: 10.1093/brain/awu408
|View full text |Cite
|
Sign up to set email alerts
|

New candidates for CD4 T cell pathogenicity in experimental neuroinflammation and multiple sclerosis

Abstract: Multiple sclerosis is a chronic autoimmune demyelinating disease of the central nervous system, which is thought to be triggered by environmental factors in genetically susceptible individuals leading to activation of autoreactive T lymphocytes. Large multi-centre genome-wide association studies have identified multiple genetic risk loci in multiple sclerosis. In this study, we investigated T cell transcriptomic changes in experimental autoimmune encephalomyelitis, an animal model for multiple sclerosis. We co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 80 publications
1
51
0
Order By: Relevance
“…However, RNAseq analysis revealed no changes in the expression in Wnt ligands or their associated receptors in the hypothalamus of Sfrp4 -/-mice. While only nine genes were differentially regulated, several, including Cd4, Odf3b and Crip1, are expressed in immune cells or regulated by inflammatory stimuli (12)(13)(14). It has also been reported SFRP4 can affect endothelial cell stability, migration and proliferation in vitro (42) and another of the hypothalamic-regulated genes, Emp1, is a component of tight junctions in the blood brain barrier (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, RNAseq analysis revealed no changes in the expression in Wnt ligands or their associated receptors in the hypothalamus of Sfrp4 -/-mice. While only nine genes were differentially regulated, several, including Cd4, Odf3b and Crip1, are expressed in immune cells or regulated by inflammatory stimuli (12)(13)(14). It has also been reported SFRP4 can affect endothelial cell stability, migration and proliferation in vitro (42) and another of the hypothalamic-regulated genes, Emp1, is a component of tight junctions in the blood brain barrier (15).…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, only 4 genes were upregulated and 5 genes were downregulated in diet-induced obese Sfrp4 -/-mice (Table 1). Interestingly, several of these genes, including Cd4, Odf3b and Crip1 have roles in immune function (12)(13)(14). Emp1 is also of interest as a tight junction protein in the blood brain barrier (15).…”
Section: Sfrp4 -/-Mice Have Reduced Bone Mineral Density (Bmd)mentioning
confidence: 99%
“…In any case, a recent study assessed the transcriptomic modification that Th17 CD4 + T cells undergo, derived from mice following induction of EAE. Interestingly, MerTK is among the genes overexpressed upon EAE induction [106]. …”
Section: Evidence About the Role Of The Gas6/tam System In Multiplmentioning
confidence: 99%
“…However, groundbreaking studies of T-cell plasticity have led to the widely accepted model that already-differentiated T cells are also able to alter their effector function in vivo. Along this line, it was demonstrated that T cells producing IFN-γ in the spinal cord during EAE originated from IL-17-producing T H 17 cells which underwent their conversion to ex-T H 17 cells by the proinflammatory cytokine IL-23 (44,45 …”
Section: Discussionmentioning
confidence: 98%